Congenital Erythropoietic Porphyria: Mutation of the Uroporphyrinogen III Cosynthase Gene in a Vietnamese Patient - Dao Hoang Thien Kim; Asako Kawazoe; Pham Dang Bang; Nguyen Tien Thanh; Shigeru Taketani (Karger Publishers, 2013)
Congenital erythropoietic porphyria (CEP) arises from an autosomal recessive inherited disorder of the porphyrin metabolism, which leads to the accumulation of uroporphyrinogen I in bone marrow, skin and several other tissues by a deficiency of uroporphyrinogen III cosynthase (UROS). We studied a Vietnamese patient and her family suffering from severe cutaneous photosensitivity with skin fragility, bullous lesions and hypertrichosis on light-exposed areas. A missense mutation in the UROS gene was identified as a transversion of G to T at nucleotide 11,776, resulting in a substitution of valine by phenylalanine at codon 3 of exon 2. The patient showed a homozygous mutant profile, and the heterozygous state was observed in the parents. The activity of mutated UROS expressed in Escherichia coli was less than 16.1% that of the control, indicating that the markedly reduced activity of UROS is responsible for CEP. We described for the first time a mutation in the UROS gene in a Southeast Asian patient and a molecular diagnosis for the identification of clinically asymptomatic heterozygous mutation carriers and families with CEP.